Mathematical Reasoning Ability and Resilience (Experiment With Senior High Students Using Inductive and Deductive Approach and Based On Student’s Cognitive Stage) - Siti Maesaroh; Utari Sumarmo; Wahyu Hidayat (IKIP Siliwangi, 2020)
The background of this study is that the unsatisfactory student’s grade on mathematical reasoning ability (MRA) tasks. Even though MRA is an ability that needs to be possessed by high school students. To overcome this problem, we carried out an experiment for improving students' MRA and mathematical resiliency (MR) through Inductive -deductive approach (IDA) and based on student’s cognitive stage (CS). The research involved 68 eleventh grade students with 16.5 years old from a high school in Bandung Indonesia. The instruments of this study were the MRA, TOLT and MR scale. The study found that as many as 29.4% student were at concrete stage, 51.5 % at transition stage, and 19.1% at formal stage. Overall and based on student’s cognitive stage, the study found that the grades of MRA and MR of students who obtained IDA were better than the grades of students who taught by discovery learning approach (DLA). Based on students' cognitive stages, there was no difference grades of MRA and MR in the two teaching approaches. Beside that, study found that there were no interaction between teaching approaches and cognitive stage on student’s MRAand MR and the IDA took higher role than the cognitive stage on obtaining student’s MRA, and MR. It was also found that students taught by DLA experienced more difficulty in completing MRA tasks. Beside that, there was moderate association between MRA, and MR, but there were no association between MRA and CS and between MR and CS. In addition, students performed active learning during the IDA lessons such as to discuss acitvely, to solve problems enthutiastically, and to present their work in front of the class voluntary